2021
DOI: 10.3389/fnagi.2021.703984
|View full text |Cite
|
Sign up to set email alerts
|

Development of α-Synuclein Real-Time Quaking-Induced Conversion as a Diagnostic Method for α-Synucleinopathies

Abstract: Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy are characterized by aggregation of abnormal α-synuclein (α-syn) and collectively referred to as α-synucleinopathy. Because these diseases have different prognoses and treatments, it is desirable to diagnose them early and accurately. However, it is difficult to accurately diagnose these diseases by clinical symptoms because symptoms such as muscle rigidity, postural dysreflexia, and dementia sometimes overlap among these diseases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 107 publications
(152 reference statements)
0
11
0
Order By: Relevance
“…First, we monitored the kinetics of fibril amplification by our HANABI assay 30,31 ( Figure 1.A ), an instrument that consists of an optimized sonoreactor equipment developed by our group, that applies ultrasonic irradiation pulses individually to each one of the wells of a 96-wells microplate, and records the ThT fluorescence in function of time, named HANABI-2000 31 . This instrument accelerates substantially the rate of fibril formation reaction compared with the traditional RT-QuIC methods 32,33 , from several days to a few hours. Then, we analyzed the morphological properties by transmission electron microscopy (TEM, Figure 1.B ).…”
Section: Resultsmentioning
confidence: 99%
“…First, we monitored the kinetics of fibril amplification by our HANABI assay 30,31 ( Figure 1.A ), an instrument that consists of an optimized sonoreactor equipment developed by our group, that applies ultrasonic irradiation pulses individually to each one of the wells of a 96-wells microplate, and records the ThT fluorescence in function of time, named HANABI-2000 31 . This instrument accelerates substantially the rate of fibril formation reaction compared with the traditional RT-QuIC methods 32,33 , from several days to a few hours. Then, we analyzed the morphological properties by transmission electron microscopy (TEM, Figure 1.B ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent developed ultrasensitive protein amplification assays, such as RT-QuIC and protein misfolding cyclic amplification (PMCA), offered an ultrasensitive approach for pathological α-syn assays ( Parnetti et al, 2019 ; Koga et al, 2021 ). This assay induces conversion of normal α-syn in samples to misfolded α-syn, allowing amplification and detection of trace amounts of pathological α-syn in tissues or biofluids ( Nakagaki et al, 2021 ). Previous studies showed that the CSF α-syn RT-QuIC had high specificity (82.3%–100%) and sensitivity (84%–100%) for the diagnosis of PD and other synucleinopathies ( Nakagaki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This assay induces conversion of normal α-syn in samples to misfolded α-syn, allowing amplification and detection of trace amounts of pathological α-syn in tissues or biofluids ( Nakagaki et al, 2021 ). Previous studies showed that the CSF α-syn RT-QuIC had high specificity (82.3%–100%) and sensitivity (84%–100%) for the diagnosis of PD and other synucleinopathies ( Nakagaki et al, 2021 ). Subsequent studies used RT-QuIC for the detection of pathological α-syn in various biospecimens, such as submandibular gland (sensitivity: 100%; specificity: 94%; Manne et al, 2020a ), olfactory mucosa (sensitivity: 46%–69%; specificity: 90%–91%; De Luca et al, 2019 ; Bargar et al, 2021 ; Stefani et al, 2021 ), skin (sensitivity: 75%–100%; specificity: 83%–100%; Hong et al, 2010 ; Manne et al, 2020b ; Donadio et al, 2021 ; Kuzkina et al, 2021 ), and saliva (sensitivity: 61.1%–76.0%; specificity: 94.4%; Luan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The real-time quaking-induced conversion (RT-QuIC) is one example of a promising new tool for measuring aggregated aSyn in CSF of PD which could be applied also to blood specimens (van Rumund et al 2019 ; Iranzo et al 2021 ). However, the value of RT-QuIC in diagnostics or for monitoring the disease course is controversial (Nakagaki et al 2021 ; van Rumund et al 2019 ). In addition, pattern recognition methods will play a major role in the identification of disease pathways, as has been previously shown in cancer research (Cheng and Zhan 2017 ).…”
Section: Current Trends In Pd Biomarker Researchmentioning
confidence: 99%